IMMU-29. LAG-3 COMPENSATES TIM-3 DOWN-REGULATION IN A HUMAN GLIOBLASTOMA MODEL. (9th November 2020) - Ogando-Rivas, Elizabeth; Castillo-Caro, Paul; Jones, Noah; Dechkovskaia, Anjelika; Yang, Changlin; Mitchell, Duane
Abstract: INTRODUCTION: There are a few alternatives treatments beside the standard care for glioblastomas, one of them is adoptive cell therapy; our group has shown promising preliminary results with a dendritic cell-based vaccine that has being tested in first-in-human clinical trials. Checkpoint inhibitors have also shown promising results in the cancer arena, but not for brain tumors. OBJECTIVE: We have assessed whether combination of checkpoint inhibition and transferred cellular therapy may enhance anti-tumor killing of adoptive T-cell therapies to improve survival in GBM patients. METHODS: PBMCs were isolated from CMV+ donors, in order to generate dendritic cells and pulsed them with CMVpp65-mRNA. DCs were co-culture with T-cells for 15-days. Five groups were made (Tim3 at 300 ug/ml, PD1, Tim3, PD1+Tim3 at 10 ug/ml and PD1+Tim3 at 3 ug/ml) and their respective isotype-control groups. IL2 was added at 100UI/ml every 3 days as well as the blockade. Phenotyping was performed on Day0 and Day15 th . Restimulation was made with pp65-pepmixes and UPGL a glioblastoma cell-line created by our group. Supernatant from overnight restimulation was analyzed for 10-cytokines. RESULTS: PD1/Tim3 condition (3ug/ml), Lag3 expression was increased in central memory T-cells (mean 19.13% vs 30.98% p=0.02). On EM T-cells, Lag3 expression increased (57.98% vs 75.83%; p=0.03); for control vs 10ug/ml from combination checkpoint treatment group. On EMRA T-cells, the results were similar, Lag3 was upregulated in response of low-doses of double checkpoint inhibitor combination (8% vs 21% p=0.002). At increased doses (Tim3 at 300ug/ml), secretion of IFN-□ was reduced in T-cells treated with Tim3 vs relevant control. Secretion of IL-12 in treated T-cells with PD1/Tim3 was significantly increased. IL-1□ secretion was significantly lower in the PD1/Tim3 (10ug/ml) treatment-group compared with control-group (p < 0.004). CONCLUSIONS: We have identified a potential activation component and dependent pathway between Tim3 and Lag3, once Tim3 and PD1 are blockade.